COMBINING ABILITY AND GENE ACTION FOR DIFFERENT CHARACTERS IN BREAD WHEAT (TRITICUM AESTIVUM L.) - A. M. RAIYANI; D. A. PATEL; V. N. KAPADIA; M. C. BOGHARA; H. C. SISARA (The Bioscan, 2015)
Combining ability analysis was studied in a 10 × 10 diallel cross of spring wheat (TriticumaestivumL.). The genotypes GAW-4, GAW-5 and GAW-8 were considered as the best general combiners, while 18 hybrids including GW-322 × LOK-1, GAW-4 × LOK-1, GAW-1 × GAW-4, GAW-2 × GW-366, GAW-2 × GW-173, GAW-5 × GAW-13, GAW-13 × LOK-1, GAW-8 × LOK-1, GAW-4 × GAW-13, GAW-8 × GAW-13 and GAW-1 × GW-366 as good specific combinations for grain yield and other yield contributing traits. The promising parents namely GAW-4 (1.15), GAW-5 (0.72) and GAW-8 (0.78) which are having high gca effects in desirable direction for yield contributing traits may be incorporated in crossing programme to have high yielding genotypes. The crosses GW-322 × LOK-1 (6.44), GAW-4 × LOK-1 (6.31), GAW-1 × GAW-4 (5.33), GAW-2 × GW-366 (5.02) and GAW-2 × GW-173 (4.87) which showed good sca effects for yield components charac- ters. In conclusion, those parents and hybrids may be exploited for higher yield by exploiting them through heterosis breeding or involving them in multiple cross breeding programme for obtaining transgressive segregants and broad genetic base population in wheat for improvement in yield.